Utilization of Rice Husk Waste in PVA-Based Hydrogel Formulation - Hardi, Gilar Wisnu; Toruan, Sari Artauli Lumban; Nurohmat; Dewi, Berlian Kusuma; Nurjanah, Suci; Efendi, Bachtiar; Winani (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The development of sustainable and cost-effective biomaterials is a primary focus in modern biomedical engineering. Addressing the critical need for circular economy solutions, this study introduces a novel ternary hydrogel composite integrating cellulose extracted from rice husk waste into a Polyvinyl Alcohol (PVA) and Guar Gum (GG) matrix. Cellulose was successfully extracted through alkalization and bleaching processes, with FTIR analysis confirming the removal of lignin and hemicellulose. The optimization of the hydrogel matrix demonstrated that a composition of 12.5% PVA and 1% Guar Gum (F2) exhibited superior mechanical properties, achieving a Tensile Strength (TS) of 10.49 MPa and Elongation at Break (EB) of 271.17%. However, the incorporation of rice husk cellulose (F3) unexpectedly resulted in a significant reduction in mechanical integrity, with TS dropping to 5.48 MPa. Uniquely, this research elucidates the mechanistic origin of this trade-off: SEM analysis provided definitive evidence that the failure was attributed to severe cellulose agglomeration and poor interfacial adhesion, which acted as structural defects. Furthermore, the study reveals a critical artifact where structural failure correlated with an increased Swelling Ratio (245.8%), proving that the observed high-water uptake was driven by passive void filling rather than true network hydrophilicity. The study concludes that while rice husk is a viable source of cellulose, simple solution blending is insufficient for reinforcement. Future research must prioritize high-energy dispersion techniques to overcome agglomeration and realize the material’s potential for biomedical applications.